Ventricular dyssynchrony assessment using ultra-high frequency ECG technique - Jurak, Pavel; Halamek, Josef; Meluzin, Jaroslav; Plesinger, Filip; Postranecka, Tereza; Lipoldova, Jolana; Novak, Miroslav; Vondra, Vlastimil; Viscor, Ivo; Soukup, Ladislav; Klimes, Petr; Vesely, Petr; et al. (Journal of interventional cardiac electrophysiology, 2017)
PURPOSE: The aim of this proof-of-concept study is to introduce new high-dynamic ECG technique with potential to detect temporal-spatial distribution of ventricular electrical depolarization and to assess the level of ventricular dyssynchrony. METHODS: 5-kHz 12-lead ECG data was collected. The amplitude envelopes of the QRS were computed in an ultra-high frequency band of 500-1000 Hz and were averaged (UHFQRS). UHFQRS V lead maps were compiled, and numerical descriptor identifying ventricular dyssynchrony (UHFDYS) was detected. RESULTS: An electrical UHFQRS maps describe the ventricular dyssynchrony distribution in resolution of milliseconds and correlate with strain rate results obtained by speckle tracking echocardiography. The effect of biventricular stimulation is demonstrated by the UHFQRS morphology and by the UHFDYS descriptor in selected examples. CONCLUSIONS: UHFQRS offers a new and simple technique for assessing electrical activation patterns in ventricular dyssynchrony with a temporal-spatial resolution that cannot be obtained by processing standard surface ECG. The main clinical potential of UHFQRS lies in the identification of differences in electrical activation among CRT candidates and detection of improvements in electrical synchrony in patients with biventricular pacing.
Keywords: výsledek terapie; Ventricular dyssynchrony; Electrocardiography; Cardiac resynchronization therapy; Cardiac Resynchronization Therapy; Male; Middle Aged; echokardiografie trojrozměrná; Image Interpretation, Computer-Assisted; Left bundle branch block; Adult; Aged; dospělí; mužské pohlaví; senioři; Ventricular Remodeling; Sampling Studies; Severity of Illness Index; Treatment Outcome; High-frequency electrocardiography; lidé; Ventricular Dysfunction, Left; ženské pohlaví; Depolarization; Humans; Echocardiography, Three-Dimensional; interpretace obrazu počítačem; dysfunkce levé srdeční komory; srdeční resynchronizační terapie; stupeň závažnosti nemoci; Female; lidé středního věku; remodelace komor; elektrokardiografie; vzorkové studie